2018
DOI: 10.3389/fpls.2018.01516
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale Analysis of the WRI-Like Family in Gossypium and Functional Characterization of GhWRI1a Controlling Triacylglycerol Content

Abstract: Cotton (Gossypium spp.) is the most important natural fiber crop and the source of cottonseed oil, a basic by-product after ginning. AtWRI1 and its orthologs in several other crop species have been previously used to increase triacylglycerols in seeds and vegetative tissues. In the present study, we identified 22, 17, 9, and 11 WRI-like genes in G. hirsutum, G. barbadense, G. arboreum, and G. raimondii, respectively. This gene family was divided into four subgroups, and a more WRI2-like subfamily was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…WRI1 affects seed oil production in plants of Zea mays (Pouvreau et al 2011), Brassica napus (Liu et al 2010;Wu et al 2014) Brachypodium distachyon (Yang et al 2015), Brassica juncea (Bhattacharya et al 2016) and Lepidium campestre (Ivarson et al 2017). Zang et al (2018) have conducted genome wide identification of wrinkled1 genes from G. hirsutum, G. barbadense, G. arboreum and G. raimondii species and have confirmed that the ectopic expression of wri1a gene from G. hirsutum can rescue the seed phenotype in wri1-7 mutant of A. thaliana. G. hirsutum was transformed to produce Ghwri1 over expressing lines and showed enhanced lipid content in seeds (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 89%
“…WRI1 affects seed oil production in plants of Zea mays (Pouvreau et al 2011), Brassica napus (Liu et al 2010;Wu et al 2014) Brachypodium distachyon (Yang et al 2015), Brassica juncea (Bhattacharya et al 2016) and Lepidium campestre (Ivarson et al 2017). Zang et al (2018) have conducted genome wide identification of wrinkled1 genes from G. hirsutum, G. barbadense, G. arboreum and G. raimondii species and have confirmed that the ectopic expression of wri1a gene from G. hirsutum can rescue the seed phenotype in wri1-7 mutant of A. thaliana. G. hirsutum was transformed to produce Ghwri1 over expressing lines and showed enhanced lipid content in seeds (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Transgenic plant generation and expression analysis were performed as previously reported [24]. Briefly, complete coding sequence of GhPDAT1d (Additional file 4) was amplified with gene specific primers from G. hirsutum acc.…”
Section: Methodsmentioning
confidence: 99%
“…Total oil content was determined with about 0.3 g seeds per sample using an NMI20-Analyst nuclear magnetic resonance spectrometer (Niumag, Shanghai, China) as previously reported [24].…”
Section: Methodsmentioning
confidence: 99%
“…Studies in rapeseed have shown that overexpression of BnWRI1 not only increases the SOC and seed mass in mature seed, but also improves chlorophyll content in developing seeds (Wu et al., 2014). GhWRI1a and GhWRI1b from cotton were highly expressed in 25‐DAP (days after pollination) developing fibers, suggesting that these two genes participate in fiber development and oil seed content (Zang et al., 2018). Knockdown of GhWRI1a expression in cotton has been found to reduce oil seed content and increase fiber length (Qaisar et al., 2017; Qu et al., 2012).…”
Section: Transcription Factors Regulating the Seed Oil Pathway In Maj...mentioning
confidence: 99%